Effectiveness of an online preparatory quiz in enhancing basic clinical skills in an introductory clinical skills course - Nurulhuda, M.H.; Norwati, D.; Ibrahim, M.S.; Zawawi, N. (2019)
Background: Research shows e-learning is effective in supporting clinical education. However, the method for its usage to improve basic clinical skills needs further guidance and evidence. Purpose: To evaluate the benefits of a preparatory online quiz on the performance of basic clinical skills in medical students. Methods: A multimodality online platform was created to assist student to learn basic clinical skills in an introductory clinical course. A comprehensive quit on clinical skills was included as one of the materials. A group of 60 students, newly-entered to clinical year session in September 2018 was ramdomized to two groups of 30 students. One group was instructed to do the online preparatory quiz prior to the start of the course. At the end of the two weeks course, all students were in evaluated individually on their basic clinical skills (BCS). t-test was applied to compare mean marks of the groups. Comparison was also made between groups which completed the quiz and the group which did not complete or attempt the quiz. Results: 26 out of 30 students attempted the online quiz, however only 21 completed it. Mean (SD) marks for BCS for attempted group was 61% (9.59) which was higher than non-attempt group marks of 57.6% (7.84). but the difference was not significant (P=0.939). However, when the students were regrouped to completed and non-completed, mean marks were 62.3% (8.65) for completed and 54.8% (8.64) for incomplete and their difference were significant (P=0.005). Conclusion: E-learning with a preparatory online quiz improved clinical skills in students with good participation in the e-learning and should be incorporated in undergraduate medical education.